16th International Congress on Antiphospholipid Antibodies Task Force Report on Catastrophic Antiphospholipid Syndrome. (October 2020) - Cervera, Ricard; Rodríguez-Pintó, Ignasi; Legault, Kim; Erkan, Doruk
Abstract: The Task Force on Catastrophic Antiphospholipid Syndrome (CAPS) met again on occasion of the 16th International Congress on Antiphospholipid Antibodies (aPL) that was held in Manchester, England, in September 2019. Its aims were to assess the up-to-date knowledge on pathogenesis, clinical and laboratory features, diagnosis and classification, precipitating factors, and treatment of CAPS. This article summarizes the main aspects that were presented during the Task Force meeting at that Congress.